Phenology of Galianthe palustris (Cham. & Schltdl.) Cabaña Fader & E. L. Cabral (Rubiaceae Juss.) in Santa Catarina plateau region (Revista de Ciências Agroveterinárias, 2021)
The objective of this study was to carry out the phenological monitoring of G. palustris over the months of July/2019 to June/2020, and to correlate with the meteorological variables in the Serra Catarinense. The intensity and synchrony of the vegetative and reproductive phenophases of 24 individuals in three areas, located in two municipalities of Santa Catarina, Brazil, were evaluated. In G. palustris, continuous sprouting was identified. The presence of mature leaves was observed throughout the period and the leaf senescence showed varying intensities. Flowering started in December extending until April. The highest percentages of flower buds present on the plants occurred from January to March and anthesis occurred from January to May, with the highest percentages in January and March. As for fruiting, the beginning was observed with the presence of immature fruits in January extending until June, but the period from January to March was identified with the highest percentages of immature fruits in the plants. The occurrence of ripe fruits was verified from February to June, with the highest percentages being recorded in February and March. The absence of senescent fruits was identified only in the months of December/2019 and January/2020, and the highest percentages occurred in the autumn and winter periods, coinciding with the presence of senescent leaves. There was a correlation between temperature and photoperiod for mature leaves, defoliation and flower buds. The synchrony of the phenological events was high for vegetative aspects and low to asynchrony for reproductive aspects. The phenological patterns of reproductive phenophase were seasonal, occurring in the summer and autumn (November to June). The vegetative phenophase occurred throughout the year, with the highest budding rates preceding the reproductive period. The results obtained provided important information about the phenology of this species in this region of occurrence.
Keywords: phenophases; medicinal plant; biodiversity; erva-de-lagarto